High performance and low complexity Max-Log-MAP algorithm for FPGA turbo decoder - Mao-Hsiu Hsu; Jhin-Fang Huang (The 7th International Conference on Advanced Communication Technology, 2005, ICACT 2005, 2005)
In this paper, we focus on implementing turbo decoder compliant with 3GPP spec, we adopted sliding window method with forward state metric as an accuracy initialization value and a modified Max-Log-MAP algorithm which modify extrinsic information by a scaling factor R. Then, we can implement the whole turbo decoder with a single-decoder structure, producing high data throughput with lower logic gates usage. The FPGA design of our proposed structure (SW-modified Max-Log-MAP) results in only 0.1 dB away from the optimal structure (SW-Log-MAP) at BER=10 -4 . It also saves about 29% hardware cost than the optimal structure